Direct and Delayed Mortality of Ceriodaphnia dubia and Rainbow Trout Following Time‐Varying Acute Exposures to Zinc. (20th July 2021) - Mebane, Christopher A.; Ivey, Christopher D.; Wang, Ning; Steevens, Jeffery A.; Cleveland, Danielle; Elias, Michael C.; Justice, James R.; Gallagher, Kathryn; Brent, Robert N.
Abstract: The potential for delayed mortality following short‐term episodic pollution events was evaluated by exposing cladocerans ( Ceriodaphnia dubia ) and rainbow trout ( Oncorhynchus mykiss ) to zinc (Zn) in various 1‐ to 48‐h and 1‐ to 96‐h exposures, respectively, followed by transferring the exposed organisms to clean water for up to 47 h for C. dubia and up to 95 h for trout for additional observation. For C. dubia, 1‐h exposures of up to 3790 µg Zn/L never resulted in mortality during the actual Zn exposures, but by 48 h, a 1‐h exposure to 114 µg/L, a concentration similar to the present US national water quality acute criterion for the test water conditions, ultimately killed 70% of C. dubia . With C. dubia, the speed of action of Zn toxicity was faster for intermediate concentrations than for the highest concentrations tested. For rainbow trout, pronounced delayed mortalities by 96 h only occurred following ≥8‐h exposures. For both species, ultimate mortalities from Zn exposures ≤8 h mostly presented as delayed mortalities, whereas for exposures ≥24 h, almost all ultimate mortalities presented during the actual exposure periods. With Zn, risks of delayed mortality following exposures to all concentrations tested were much greater for the more sensitive, small‐bodied invertebrate ( C. dubia ) than for the less sensitive, larger‐bodied fish (rainbow trout). These results, along with previous studies, show that delayed mortality is an important consideration in evaluating risks to aquatic organisms from brief, episodic exposures to some substances. Environ Toxicol Chem 2021;40:2484–2498. © 2021 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC. This article has been contributed to by US Government employees and their work is in the public domain in the USA. Abstract : Rainbow trout could withstand extreme Zn pulses of 1 to 3 h, with few subsequent deaths. Few Ceriodaphnia dubia died during 1‐ to 3‐h Zn pulses, but after 48 h, most were dead. Time to effects decreased as expected as rainbow trout were exposed to increasing Zn concentrations. Not so with C. dubia : time to effects was fastest in intermediate Zn exposures, with longer survivals in higher Zn exposures.